Children’s Nurses’ Knowledge and Attitudes on Paediatric Pain: A Descriptive Cross-Sectional Survey in a Developing Country - Oduro, Evans; Diji, Abigail Kusi-Amponsah; Kusi, Grace; Amagyei, Albert; Kyei-Dompim, Joana; Lomotey, Alberta; Boateng, Edward Appiah; Budu, Hayford Isaac (Nurse Media Journal of Nursing, 2020)
Background: Children’s nurses’ knowledge of pain affects their pain management practices. Even though poor knowledge and attitudes have been reported in several studies, most were carried out in developed settings. However, little has been reported on the management of paediatric pain by nurses in resource-limited settings such as in sub-Saharan Africa.Purpose: This study sought to assess the knowledge and perceptions of children’s nurses regarding paediatric pain in a Ghanaian context.Methodology: A descriptive cross-sectional survey was carried out among 65 nurses at eight hospitals at various levels of healthcare in Ghana. Over three months, participants’ demographic data and responses on the Pediatric Nurses Knowledge and Attitude Survey Regarding Pain (PNKAS) instrument were collected. Data were analyzed and presented using descriptive and inferential statistics.Results: Participants’ average (SD) knowledge and attitudes regarding paeditric pain was 36.7% (6.9%) and ranged from 21.4% to 57.1%. Pediatric pain knowledge and attitudes (PPKA) of the nurses differed based on working years in the children’s unit and the hospital type they worked in (p<0.05). Nevertheless, the type of hospital facility was the only independent predictor of their PPKA (R2=0.181, p<0.001).Conclusion: Children nurses in this setting generally had insufficient knowledge and attitudes on paediatric pain. They should be motivated to undertake self-directed learning and regular continuing professional education to update their knowledge, attitude and skills on evidence-based pediatric pain assessment and management.